2021
DOI: 10.1101/2021.09.21.460794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PCDH7 Promotes Cell Migration by Regulating Myosin Activity

Abstract: Cell migration requires spatiotemporally coordinated activities of multicomponent structures including the actomyosin cortex, plasma membrane, adhesion complexes and the polarity proteins. How they function together to drive this complex dynamic process remains an outstanding question. Here, we show that a member of the protocadherin family, PCDH7 displays a polarized localization in migratory cells with a dynamic enrichment at the leading and rear edges. Perturbation of PCDH7 interferes with the migration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…Previously it was reported that PCDH7 increases phospho-myosin light chain levels to enhance anchorageindependent cell growth (Wang et al, 2020). Similarly, in a parallel study, we observed that PCDH7 overexpression enhances phospho-myosin levels during cell migration in Retinal Pigment Epithelial (RPE) cells and PCDH7 interacts with PP1cβ, the catalytic subunit, and MYPT1, the myosin targeting subunit of myosin phosphatase holoenzyme (Qureshi et al, 2021). Previous studies also reported that PCDH7 behaves as a signaling molecule more than an adhesion molecule and inhibits phosphatase activities of PP1a and PP2A (Wang et al, 2020;Zhou et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…Previously it was reported that PCDH7 increases phospho-myosin light chain levels to enhance anchorageindependent cell growth (Wang et al, 2020). Similarly, in a parallel study, we observed that PCDH7 overexpression enhances phospho-myosin levels during cell migration in Retinal Pigment Epithelial (RPE) cells and PCDH7 interacts with PP1cβ, the catalytic subunit, and MYPT1, the myosin targeting subunit of myosin phosphatase holoenzyme (Qureshi et al, 2021). Previous studies also reported that PCDH7 behaves as a signaling molecule more than an adhesion molecule and inhibits phosphatase activities of PP1a and PP2A (Wang et al, 2020;Zhou et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…Of note, the over-representation of responses to me- Modulated SMCs express SMC genes, such as CNN1, and ITGA8, but show significant upregulation of "synthetic" markers like MYH10, FN1, and COL8A1 (Figure 5B, Data Set S1). Proinflammatory adhesion molecules (ALCAM) [53], promigratory mediators (PCDH7) [54], and modulation regulators (SPINT2) [55] are also upregulated in this subcluster. High levels of MYH10, FN1, COL8A1, and POSTN are also defining features of activated fibroblasts, along with significant upregulation of the thrombin receptor F2R, and the integrin ITGA10 (shared by arterial modulated SMCs).…”
Section: Phenotypic Differences In Myofibroblastic Populations Explai...mentioning
confidence: 89%